REVIVAL OF UKRAINIAN BLACKSMITHING: ART PRACTICES AND EDUCATION DURING THE 1970S–2010S - Rohotchenko, Svitlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article is aimed at making an outline of the revival process experienced by professional Ukrainian blacksmithing art, development of which resumed in the 1970s, after an imposed pause that had lasted for over half a century. The facts from the history of development and further evolution of blacksmithing are publicized, as well as the reasons that caused almost complete distinction of traditional blacksmithing handicraft and professional blacksmithing art as a result of suppression by the Soviet power. The objective of the research is a real-time coverage of the stages of revival of blacksmithing craft, art, and education. Extermination of the traditional blacksmithing education that existed in Ukraine since the 16th century and up till 1917 took its toll. Young blacksmiths were trained in the forges where they worked as assistants. The first departments of artistic blacksmithing were established in the colleges, technical schools, institutes, and academies only in the late 1980s. Lack of specialized education was a drawback for Ukrainian blacksmithing comparing to the European states where there was no gap in training practice. In the article, the most well-known modern Ukrainian blacksmithing educational institutions are analyzed on the basis of historical method, chronological and cultural approaches.